Applanation tonometry: a comparison of the Perkins handheld and Goldmann slit lamp-mounted methods - Arora, R (Dove Medical Press, 2014)
PURPOSE: To compare intraocular pressure (IOP) measurements, taken using Perkins applanation tonometry (PAT) and Goldmann applanation tonometry (GAT). METHODS: 100 eyes of 100 patients underwent Perkins and Goldmann applanation tonometry, with a randomized order of modality, performed by a masked observer. The right eye was measured, for all subjects, and the data used in statistical analysis. The comparability of results given by the two instruments was evaluated using the Bland–Altman method. RESULTS: IOP measurements for 100 eyes were obtained (range: 10–44 mmHg). The mean GAT reading was 21.63 mmHg, with standard deviation (SD) 5.69 mmHg. The mean PAT reading was 21.40 mmHg, with SD 5.67 mmHg. The mean difference between readings from Goldmann versus Perkins tonometry was 0.22 mmHg (SD: 0.44 mmHg). The limits of agreement were calculated to be −0.64–+1.08 mmHg (1.96 SD either side of the bias). CONCLUSION: The Perkins applanation tonometer yields IOP measurements that are closely comparable with GAT. Therefore, PAT may be used in routine clinical practice, as part of the implementation of national guidelines, or preferred practice patterns, for glaucoma and ocular hypertension.